The basic biology of erbB-2 and its participation in colorectal cancers - Stawińska, Magdalena; Bryś, Magdalena; Krajewska, Wanda M. (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2005)
ErbB-2 is one of Tour cell surface growth factor receptors involved in transmission of signals controlling normal cell growth and differentiation. A range of growth factors serve as ligands, but none is specific for the ErbB-2 receptor. Ligand binding to ErbB-1, ErbB-3 and ErbB-4 induces rapid receptor dimerization, with a marked preference for ErbB-2 as a dimer partner. When ErbB-2 is overexpressed multiple ErbB-2 heterodimers are formed and cell signalling is stronger, resulting in enhanced responsiveness to growth factors and malignant growth. This explains why ErbB-2 overexpression is an indicator of poor prognosis in colorectal cancers and may be predictive of response to treatment. ErbB-2 is a highly specific and promising target for new colon cancer treatments.